Structural evolution of the double perovskites Sr2B'UO6 (B' = Mn, Fe, Co, Ni, Zn) upon reduction: Magnetic behavior of the uranium cations - Pinacca, Ruben Miguel (2011)
We describe the preparation of five perovskite oxides obtained upon reduction of Sr2B′UO6 (B′ = Mn, Fe, Co, Ni, Zn) with H2/N2 (5%/95%) at 900 °C during 8 h, and their structural characterization by X-ray powder diffraction (XRPD). During the reduction process there is a partial segregation of the elemental metal when B′ = Co, Ni, Fe, and the corresponding B′O oxide when B′ = Mn, Zn. Whereas the parent, oxygen stoichiometric double perovskites Sr2B′UO6 are long-range ordered concerning B′ and U cations. The crystal structures of the reduced phases, SrB′0.5−xU0.5+xO3 with 0.37 < x < 0.27, correspond to simple, disordered perovskites; they are orthorhombic, space group Pnma (No. 62), with a full cationic disorder at the B site. Magnetic measurements performed on the phase with B′ = Zn, indicate uncompensated antiferromagnetic ordering of the U5+/U4+ sublattice below 30 K.